2020
DOI: 10.1364/oe.389814
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of a shopping mall with flexible OLED-based visible light communications

Abstract: Visible light communications (VLC) can utilize light-emitting diodes (LEDs) to provide illumination and a safe and low-cost broadcasting network simultaneously. In the past decade, there has been a growing interest in using organic LEDs (OLEDs) for soft lighting and display applications in public places. Organic electronics can be mechanically flexible, thus the potential of curved OLED panels/displays devices. This paper provides unique characteristics of a flexible OLED-based VLC link in a shopping mall. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…For the considered scenario, we have used the non-sequential ray tracing method to determine the detected optical power and the path lengths between the Tx and the Rx. Note, the CIR is expressed as [20]:…”
Section: Simulation Environmentmentioning
confidence: 99%
“…For the considered scenario, we have used the non-sequential ray tracing method to determine the detected optical power and the path lengths between the Tx and the Rx. Note, the CIR is expressed as [20]:…”
Section: Simulation Environmentmentioning
confidence: 99%
“…All these inputs are processed as a source of big data to provide tourism stakeholders with valuable information about the behavior and preferences of each segment of travelers and their responses to commercial stimuli, in what is now known as the Internet of Behavior (IoB). These applications are especially suitable for the orientation and management of information in museums [ 32 , 33 ], commercial areas [ 34 ], and cultural facilities [ 35 ], where the directionality of the optical links and their intrinsically cellular character, being confined by the walls, becomes an advantage, e.g., we can discriminate what specific picture is being contemplated or what type of products attract a tourist to a store. Some experimental experiences have already been verified in the use of VLC systems to allow automatic hotel check-in, where the cellphone screen acts as a “key” for the verified hotel room access system [ 36 ].…”
Section: Ict and Smart Tourism: Trends And Scenariosmentioning
confidence: 99%
“…It evolves the specification and location of the Tx and the Rx, features of the CAD models of objects, wavelength-dependent reflectance of surfaces (wall, ceiling, floor, and objects), and transmission/reflection coefficient of glass windows. Next, the captured output data of the OpticStudio ® is processed in MATLAB to obtain the CIR expressed as given by [27,32]:…”
Section: Simulation Featuresmentioning
confidence: 99%
“…The recorded results in [31] reveals the ability of OLED based VLC system to achieve R b of 4 Mb/s with a bit-error-rate (BER) below the forward error correction BER limit. In [32], investigating of a flexible OLED-based VLC link in a shopping mall was reported, in both empty and furnished rooms using both full and half-circular OLEDs. The results indicated that, the OPL in an empty room is about 5 dB less than the furnished room.…”
Section: Introductionmentioning
confidence: 99%